Rationale of family medicine physicians in effectively identifying patients with chronic hyperglycemia through point-of-care hemoglobin A1C screenings - Whitley, Heather P. (J Diabetes Metab Disord, 2019)
PURPOSE: Many patients are unknowingly living with chronic hyperglycemia, possibly due to low screening rates. We aimed to correlate detection of unidentified chronic hyperglycemia to practitioner reported rationale for conducting diabetes screening. METHODS: Physicians screened patients via a point-of-care A1C tests and recorded corresponding rationales. Elevated outcomes (A1C ≥ 5.7%) were correlated to recorded rationales, frequency of repeat screenings, documented diagnoses, and therapeutic actions taken as a result of elevated A1C. RESULTS: Nearly one-half (45%) of selected patients were unknowingly living with chronic hyperglycemia, having an average A1C of 7.92% for outcomes ≥6.5%. Most commonly recorded rationales were overweight status (71%), high-risk ethnicity (58%), and age > 45 years (48%); previously recorded A1C result of ≥5.7% (χ(2) 16.02, p < 0.001) and hypertension diagnosis (χ(2) 10.37, p = 0.0013) showed statistically significant correlation with elevated A1C outcomes. A1C results ≥6.5% versus 5.7–6.5% more frequently prompted repeat screenings (77% vs 20%), ICD-10 code documentation (91% vs 28%), lifestyle modification recommendations (78% vs 35%), and drug therapy initiation (78% vs 9%). CONCLUSIONS: Reported rationales were largely impacted by visual inspections of age, race, and weight, and prediabetic A1C values garnered less attention compared to higher values. Utilization of POC A1C screening followed by conformational repeat testing is a practical approach to improve diagnostic rates and initiation of care for diabetes.